Environmental contaminants in New Zealand’s endemic, endangered Hector’s dolphin (Cephalorhynchus hectori) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Albany, New Zealand - Casano-Bally, Déborah (Massey University, 2023)
Due to their coastal distribution, Hector’s (Cephalorhynchus hectori hectori) and subspecies Māui (C. h. maui) dolphins are exposed to land runoff and point source inputs. However, little focus has been placed on contaminant burdens, which in the context of increased disease mortality affecting the species, is of concern. Several persistent environmental pollutants are known immunosuppressants, enhancing disease susceptibility. Here I applied generalised linear models to examine the spatiotemporal trends in contaminant burden while accounting for the effects of total body length (TBL) and sex. Polychlorinated biphenyls (PCBs, 45 congeners), multi-residue pesticides (∑DDT, HCB, oxychlordane, dieldrin and mirex) and polybrominated diphenyl ethers (PBDEs, 10 congeners) were analysed in the blubber of Hector’s and Māui dolphins (n = 66; 30 males and 36 females) stranded or by-caught in New Zealand between 1997 and 2022. For both ∑PCB and ∑MRP, sex was the most important predictor, followed by total body length (TBL). In males, PCB and MRP burden increased with increasing TBL, while this trend was less pronounced in females. Dolphins from the east coast of New Zealand recorded the highest overall PCB and MRP burdens. Despite being legacy contaminants banned over 30 years ago, year was the least important predictor, with minimal to no decline observed in concentrations of ∑PCB, ∑MRP, ∑DDT and HCB over the 25-year study period. For PBDEs, the most important predictor was TBL, followed by sex. Concentrations increased with TBL and were highest in males. However, no interaction between sex and TBL was observed, indicating no difference in the effects of TBL between males and females. This may signal less offloading for females during pregnancy and lactation compared to other contaminants assessed. PBDE burdens were lowest in animals from the west coast. While a marginal decline in PBDE burden over time was noted, this had almost no contribution to the overall model fit. Results show that older animals have higher concentrations than younger animals, likely due to the accumulation of contaminants in the tissues over time. Our study provides important knowledge needed to guide appropriate conservation actions, especially in the context of disease susceptibility, including but not limited to toxoplasmosis.
Keywords: 410501 Environmental biogeochemistry